2011
DOI: 10.1007/s00403-011-1129-9
|View full text |Cite
|
Sign up to set email alerts
|

Influence of endothelial nitric oxide synthase polymorphisms in psoriasis risk

Abstract: Abstract:Nitric oxide (NO) is a potent regulator of keratinocyte growth and differentiation that has been implicated in the pathogenesis of psoriasis (Ps). The NOS3 -786 T/C (SNP id rs2070744; www.ensembl.org ), intron 4 variable number tandem repeat (VNTR), and Glu298Asp (SNP id rs1799983) polymorphisms, have been associated with differences in NO plasma concentrations and with the risk of hypertension (HT) and ischemic cardiac disease (IC). The aim of this study was to determine whether the above mentioned N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 34 publications
0
15
0
1
Order By: Relevance
“…Our data suggest that WD specifically activated TGR5 signaling in dermatitic lesions. Activated TGR5 in the dermatitis mice increased Nos3 expression, which likely leads to increased production of nitric oxide, a potent regulator for the growth and differentiation of keratinocytes and is implicated in the pathogenesis of and risk for developing psoriasis [42,43]. TGR5 activation in dermatitic lesions was also demonstrated by the induction of Trpa1 and Trpv1, which are the downstream mediators of many pruritogenic pathways.…”
Section: Discussionmentioning
confidence: 98%
“…Our data suggest that WD specifically activated TGR5 signaling in dermatitic lesions. Activated TGR5 in the dermatitis mice increased Nos3 expression, which likely leads to increased production of nitric oxide, a potent regulator for the growth and differentiation of keratinocytes and is implicated in the pathogenesis of and risk for developing psoriasis [42,43]. TGR5 activation in dermatitic lesions was also demonstrated by the induction of Trpa1 and Trpv1, which are the downstream mediators of many pruritogenic pathways.…”
Section: Discussionmentioning
confidence: 98%
“…Endothelin-1 levels were correlated with psoriasis activity, and oxidative stress may play a role by destructive effects of reactive oxygen species, damaging endothelium-dependent vasodilatation. 7,16,17 OR, odds ratio. The main factors associated with psoriasis and hypertension in men are diabetes and obesity, whereas in women they are smoking and obesity (Table 2).…”
Section: Discussionmentioning
confidence: 99%
“…As mentioned earlier, recent studies have also found interleukin 1β ( IL-1β ), tumor necrosis factor ( TNF ) [ 47 ], vitamin D receptor ( VDR ) [ 48 ], nitric oxide synthase 3 ( NOS3 ) [ 49 ], and other genes to be overexpressed in psoriasis patients (GOF). Therefore, we used inhibitors for these targets and in turn designed drug repositioning strategies for psoriasis.…”
Section: Implications For Drug Repositioningmentioning
confidence: 99%